6p-49=11p-79

Simple and best practice solution for 6p-49=11p-79 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6p-49=11p-79 equation:


Simplifying
6p + -49 = 11p + -79

Reorder the terms:
-49 + 6p = 11p + -79

Reorder the terms:
-49 + 6p = -79 + 11p

Solving
-49 + 6p = -79 + 11p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-11p' to each side of the equation.
-49 + 6p + -11p = -79 + 11p + -11p

Combine like terms: 6p + -11p = -5p
-49 + -5p = -79 + 11p + -11p

Combine like terms: 11p + -11p = 0
-49 + -5p = -79 + 0
-49 + -5p = -79

Add '49' to each side of the equation.
-49 + 49 + -5p = -79 + 49

Combine like terms: -49 + 49 = 0
0 + -5p = -79 + 49
-5p = -79 + 49

Combine like terms: -79 + 49 = -30
-5p = -30

Divide each side by '-5'.
p = 6

Simplifying
p = 6

See similar equations:

| 9p+146=8p | | 4x-207=9-5x | | 20x+15y=950 | | z^2+2zi-2=0 | | -9(t^2+13)(t^2-7)=0 | | 48x=4.176 | | -4+14-24=x | | 8v+80=17v-100 | | 3x-11=4x-11 | | 0.05x=0.0815 | | 46b-42b+9b+10b-21b-1=39 | | 19c+45=31c-63 | | 5g+6kg=g | | (X*x)+((3x)*(3x))=(24*24) | | 10b-9b+7b+3b+1=45 | | 45h+11=34h+55 | | 12a-11a-a+11a+3=36 | | 7×1/2= | | (X-3)(x^2+4x+19)=0 | | 5g+6k=g | | 10x+5=2x-8x | | 15x^5-5/5x^4-10 | | 9q-5q+4q-6q-2=14 | | -4x^2-32x-48=0 | | (-3x-4y)(9x^2-12xy+16y^2)= | | I=1000-40(7) | | -2(3x+5)-2x=x-43 | | -4/11x=8/99 | | 2.25x+5=13.5t+14 | | 252=(4+y)16.8 | | 4(x+2)=4(x+13) | | -8x+36= |

Equations solver categories